Certified Information Security Manager (CISM) Cert Prep (2022): 2 Information Security Risk Management. - Chapple, Mike (linkedin.com, 2022)
Prepare to pass the Certified Information Security Manager (CISM) exam. Explore the detailed information you need to prepare for the Information Risk Management exam domain.